Plasma cells in human pancreatic ductal adenocarcinoma secrete antibodies against self-antigens - Min Yao; Jonathan Preall; Johannes T.-H. Yeh; Darryl Pappin; Paolo Cifani; Yixin Zhao; Sophia Shen; Philip Moresco; Brian He; Hardik Patel; Amber N. Habowski; Daniel A. King; et al. (JCI Insight, 2023)
Intratumoral B cell responses are associated with more favorable clinical outcomes in human pancreatic ductal adenocarcinoma (PDAC). However, the antigens driving these B cell responses are largely unknown. We sought to discover these antigens by using single-cell RNA sequencing (scRNA-Seq) and immunoglobulin (Ig) sequencing of tumor-infiltrating immune cells from 7 primary PDAC samples. We identified activated T and B cell responses and evidence of germinal center reactions. Ig sequencing identified plasma cell (PC) clones expressing isotype-switched and hypermutated Igs, suggesting the occurrence of T cell–dependent B cell responses. We assessed the reactivity of 41 recombinant antibodies that represented the products of 235 PCs and 12 B cells toward multiple cell lines and PDAC tissues and observed frequent staining of intracellular self-antigens. Three of these antigens were identified: the filamentous actin (F-actin), the nucleic protein RuvB like AAA ATPase 2 (RUVBL2), and the mitochondrial protein heat shock protein family D (Hsp60) member 1 (HSPD1). Antibody titers against F-actin and HSPD1 were substantially elevated in the plasma of patients with PDAC compared with healthy donors. Thus, PCs in PDAC produce autoantibodies reacting with intracellular self-antigens, which may result from promotion of preexisting, autoreactive B cell responses. These observations indicate the chronic inflammatory microenvironment of PDAC can support the adaptive immune response.